PENGARUH LOKASI, PROMOSI, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI KOI MEGA KUNINGAN - Bangkit Saputra; Meylani Tuti (Human Capital Development, 2022)
The purpose of this study was to analyze and determine the effect of location, promotion, and service quality on purchasing decisions at KOI Mega Kuningan. The population in this study were visitors to KOI Mega Kuningan. The sampling technique used was accidental sampling with 100 respondents. The analytical method used is multiple linear regression. The results showed that location, promotion, service quality had an influence on purchasing decisions either partially or simultaneously.